Event marketing : how to successfully promote events, festivals, conventions, and expositions - Preston, C. A. (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
A modern, completely updated guide to effective event marketing As the events market becomes increasingly saturated, it is essential for a successful event professional to understand the use of strategic marketing plans. Events are everywhere-in the U.S. alone, there are more than 2,500 music festivals a year, for example, while the UK hosts over 70 different beer festivals each year. In such a crowded market, how can the event planner ensure that his or her event stands out? Marketing expert Chris Preston has the answers in this second edition of Event Marketing . From the basics of promoting an event to the use of events as marketing strategies themselves, Preston provides straightforward advice and information on all the latest Event Marketing techniques. The book begins with sections on what " Event Marketing " really means, and how the field has evolved throughout time. Preston then explores Event Marketing strategies from both a conceptual and practical standpoint, and provides information on sponsorship and corporate branding. The book covers marketing for all types of events, including festivals, corporate and association events, and social functions, and a full chapter on digital Event Marketing covers all the latest e-marketing strategies. Case studies provide real-world examples of successful marketing efforts, while Discussion Questions for each chapter provide opportunities for further exploration of key concepts. As marketing becomes an increasingly important skill for event management professionals, this completely revised second edition of Event Marketing will be a must-have for working professionals, students, and aspiring event planners everywhere.
1. What is an Event and What is Event Marketing? -- 2. The Evolution of Event Marketing -- 3. The Theory and Practice of Event Marketing -- 4. Sponsorship and Cause-Related Event Marketing -- 5. E-Event Marketing -- 6. Entertainment and Festival Event Marketing -- 7. Corporate Event Marketing -- 8. Association, Convention and Exhibition Event Marketing -- 9. Social Event Marketing -- 10. Future Forces and Trends in Event Marketing -- 11. Event Marketing Case Studies -- 12. Resources.
Includes bibliographical references and index.
Keywords: MARKETING